Aspectos da cienciometria aplicados a um estudo de caso: área de Letras - Favato, Vânia Aparecida Marques [UNESP]; Godinho, Pedro Henrique [UNESP] (Pontifícia Universidade Católica de Campinas, 2005)
This article originated from a master's dissertation, submitted to the Graduate Program in Sciences of Information at the Pontifícia Universidade Católica de Campinas. Such dissertation conducted an analysis of citations of bibliographical references/bibliography found in theses and dissertations submitted during the years 1999 to 2002, in the following areas of Letters: Linguistics, Literary Theory, and Comparative Literature. Those theses had been conducted in departments of three state universities in São Paulo state: Faculdade de Filosofia, Ciências e Letras at Universidade de São Paulo, in the state capital; Faculdade de Ciências e Letras at Universidade Estadual Paulista Júlio de Mesquita Filho, in the city of Assis; and Instituto de Estudos da Linguagem at Universidade Estadual de Campinas, in the county of Campinas. The occurrences of document citations were verified in electronic support, by means of the scientometric method. Aspects related to the characteristics of the documents were registered, such as: books, articles in periodicals, scientific events, theses and dissertations. Citations of documents retrieved by means of electronic media, and citations of printed documents were compared quantitatively. A sample of 229 theses and dissertations was selected, out of a total of 539 works concluded in the above mentioned universities. By means of semi-structured interviews, quality indicators were obtained regarding the dissemination policies for printed and electronic documents in the Humanities, particularly in the area of Letters. The period covered by the research had its starting year defined by the implementation of Program of Electronic Library, by the São Paulo State Foundation for Research Support, which provided the state's public universities with the access to electronic journals.

O presente artigo originou-se do conteúdo desenvolvido na dissertação de mestrado, apresentada ao Programa de Pós-Graduação em Ciência da Informação da Pontifícia Universidade Católica de Campinas, na qual procedeu-se a uma análise das citações de referências bibliográficas/bibliografia consultadas, das teses e dissertações nas subáreas de Lingüística e Teoria Literária e Literatura Comparada, produzidas no período de 1999 a 2002, nas faculdades de Letras das seguintes universidades estaduais paulistas: Universidade de São Paulo - Faculdade de Filosofia, Letras e Ciências Humanas; Universidade Estadual de São Paulo Júlio de Mesquita Filho - Faculdade de Ciências e Letras de Assis e Universidade Estadual de Campinas - Instituto de Estudos da Linguagem. Verificou-se a incidência das citações de documentos em suporte eletrônico, a partir do método cienciométrico. Foram detectados aspectos referentes às características dos documentos citados, tais como livros, artigos de periódicos, eventos científicos, teses e dissertações. Compararam-se quantitativamente as citações de documentos em suporte eletrônico e as citações de documentos impressos, a partir de uma amostra estratificada de 229 teses e dissertações, de um total de 534 trabalhos defendidos nas referidas universidades. Através de entrevistas semi-estruturadas, foram obtidos indicadores de qualidade para as políticas de divulgação de documentos impressos e eletrônicos para as Ciências Humanas, especificamente para a área de Letras. O período examinado na pesquisa foi definido a partir do ano da implantação do Programa de Biblioteca Eletrônica, pela Fundação para Amparo da Pesquisa do Estado de São Paulo, que possibilitou o acesso a periódicos eletrônicos para as universidades públicas paulistas.
Scientometric's aspects applied to a study of case: Letters courses
Keywords: cienciometria; banco de dados; pesquisa científica - Letras; scientometrics; database; scientific production; electronic documents; research in languages